Conjugation of metronidazole with dextran: a potential pharmaceutical strategy to control colonic distribution of the anti-amebic drug susceptible to metabolism by colonic microbes - Kim W; Yang Y; Kim D; Jeong S; Yoo J; Yoon JH; Jung Y (Dove Medical Press, 2017)
Wooseong Kim, Yejin Yang, Dohoon Kim, Seongkeun Jeong, Jin-Wook Yoo, Jeong-Hyun Yoon, Yunjin Jung Laboratory of Biomedicinal Chemistry, Department of Manufacturing Pharmacy, College of Pharmacy, Pusan National University, Busan, Republic of Korea Abstract: Metronidazole (MTDZ), the drug of choice for the treatment of protozoal infections such as luminal amebiasis, is highly susceptible to colonic metabolism, which may hinder its conversion from a colon-specific prodrug to an effective anti-amebic agent targeting the entire large intestine. Thus, in an attempt to control the colonic distribution of the drug, a polymeric colon-specific prodrug, MTDZ conjugated to dextran via a succinate linker (Dex-SA-MTDZ), was designed. Upon treatment with dextranase for 8 h, the degree of Dex-SA-MTDZ depolymerization (%) with a degree of substitution (mg of MTDZ bound in 100 mg of Dex-SA-MTDZ) of 7, 17, and 30 was 72, 38, and 8, respectively, while that of dextran was 85. Depolymerization of Dex-SA-MTDZ was found to be necessary for the release of MTDZ, because dextranase pretreatment ensures that de-esterification occurs between MTDZ and the dextran backbone. In parallel, Dex-SA-MTDZ with a degree of substitution of 17 was found not to release MTDZ upon incubation with the contents of the small intestine and stomach of rats, but it released MTDZ when incubated with rat cecal contents (including microbial dextranases). Moreover, Dex-SA-MTDZ exhibited prolonged release of MTDZ, which contrasts with drug release by small molecular colon-specific prodrugs, MTDZ sulfate and N-nicotinoyl-2-{2-(2-methyl-5-nitroimidazol-1-yl)ethyloxy}-d,l-glycine. These prodrugs were eliminated very rapidly, and no MTDZ was detected in the cecal contents. Consistent with these in vitro results, we found that oral gavage of Dex-SA-MTDZ delivered MTDZ (as MTDZ conjugated to [depolymerized] dextran) to the distal colon. However, upon oral gavage of the small molecular prodrugs, no prodrugs were detected in the distal colon. Collectively, these data suggest that dextran conjugation is a potential pharmaceutical strategy to control the colonic distribution of drugs susceptible to colonic microbial metabolism. Keywords: dextran–metronidazole conjugate, colon-specific prodrug, metronidazole, dextran, polymeric prodrug, controlled release